Permainan Tradisional Statak Meningkatkan Aspek Perkembangan Agama Dan Moral Anak - Tri Utami, Dian; Raihana, Raihana; Wahyuni, Ida Windi (UIR Press, 2022)
The low religious and moral values ​​of the nation's children are reflected in the many criminal cases that occur, such as sexual harassment, violence, bullying, corruption, dishonesty, self-destruction with drugs and free sex. This case no longer views adulthood as the culprit, but has occurred at a young age and even at an early age. Religious and moral education from an early age is an important effort to create individuals who have good morals, have ethics, have concern and continue to learn like teachings in Islam. The purpose of this research is to produce a product and determine the feasibility of a traditional statak game product as a nation's wealth in helping to develop children's religious and moral values ​​from an early age as a provision to be able to judge something in the life of the next child in society. This development research uses the Borg and Gall theory development procedure which is simplified and includes 5 stages. The trial stage cannot be carried out on students because schools are closed due to COVID-19 that hit Indonesia. Data collection using a questionnaire. The results of the validation of material experts and media experts were 86.3% classified as very feasible, the results of educator validation of 96% classified as very feasible. Thus the Statak traditional game is declared feasible to be used in learning. This research produces a traditional statak game tool (statak bag). The researcher suggests that this traditional game be included in the learning program.